GEOCHEMICAL, MINERALOGICAL, AND PETROGRAPHICAL STUDIES OF IRONSTONES AROUND MOUNT PATTI, SOUTHERN BIDA BASIN, NIGERIA: IMPLICATIONS FOR QUALITY ASSESSMENT, PROVENANCE AND ENVIRONMENT OF DEPOSITION - Ayuba, R.; Baba, Y.; Adamu, L. M.; Ochu, G. D.; Ebe, A.; Emmanuel, A. U. (FUDMA JOURNAL OF SCIENCES, 2024)
The mineralogical composition, geochemistry, and depositional environment of the ironstone exposed on Mount Patti in the southern Bida Basin of Nigeria were assessed using integrated geochemical, mineralogical, and petrographic techniques. X-ray fluorescence spectrometry, X-ray diffraction, and transmitted light microscopy were used in geochemical, and petrographical investigations of fourteen representative ironstone samples. Average chemical analysis results showed that the concentrations of SiO2 (5.93 wt%), TiO2 (0.09 wt%), Al2O3 (10.76 wt%), and Fe2O3 (77.47 wt%) were as follows. The ironstone may be found in a shallow marine environment or non-marine environment if the concentrations of CaO, Na2O, K2O, MnO, and CuO are less than 0.40. This assertion is supported by the absence of sulfur oxide (SO3) in the examined samples and the bivariate plot of SiO2 versus Al2O3 and triangular plot of Fe-Mn-(Cu+Zn). Low levels of CaO and the absence of CO3 indicate that the environment is oxidizing. The iron's grade was calculated and found to be approximately 54.180%, which has been classified as low grade. The study also revealed that the ironstone contains a high amount of gangue materials (Al2O3 and P2O5), its silica (SiO2) content is within permissible limits, and it is devoid of harmful materials like sulfur. Based on petrographic studies, the floating contact displayed by the framework grains indicates that the iron cements were eodiagenetic in origin. Although it can be used more effectively as cast iron, sufficient beneficiation (to remove excess silica) can make it useful for iron and steel production.
Keywords: Hematite; Provenance; Agbaja ironstone; Mount Patti; Nigeria